The impact of environmental temperature deception on perceived exertion during fixed-intensity exercise in the heat in trained-cyclists - Borg, D. N.; Stewart, I. B.; Costello, J. T.; Drovandi, C. C.; Minett, G. M. (Physiology & Behavior, 2018)
Purpose: This study examined the effect of environmental temperature deception on the rating of perceived exertion (RPE) during 30 min of fixed-intensity cycling in the heat. Methods: Eleven trained male cyclists completed an incremental cycling test and four experimental trials. Trials consisted of 30 min cycling at 50% Pmax, once in 24 °C (CON) and three times in 33 °C. In the hot trials, participants were provided with accurate temperature feedback (HOT), or were deceived to believe the temperature was 28 °C (DECLOW) or 38 °C (DECHIGH). During cycling, RPE was recorded every 5 min. Rectal and skin temperature, heart rate and oxygen uptake were continuously measured. Data were analysed using linear mixed model methods in a Bayesian framework, magnitude-based inferences (Cohens d), and the probability that d exceeded the smallest worthwhile change. Results: RPE was higher in the heat compared to CON, but not statistically different between the hot conditions (mean [95% credible interval]; DECLOW: 13.0 [11.9, 14.1]; HOT: 13.0 [11.9, 14.1]; DECHIGH: 13.1 [12.0, 14.2]). Heart rate was significantly higher in DECHIGH (141 b·min-1 [132, 149]) compared to all other conditions (DECLOW: 138 b·min-1 [129, 146]; HOT: 138 b·min-1 [129, 145]) after 10 min; however, this did not alter RPE. All other physiological variables did not differ between the hot conditions. Conclusion: Participants were under the impression they were cycling in different environments; however, this did not influence RPE. These data suggest that for trained cyclists, an awareness of environmental temperature does not contribute to the generation of RPE when exercising at a fixed intensity in the heat.